Using infographics and video to prevent injuries and illnesses in athletics - Edouard, P.; Branco, P.; Glover, D.; Duncan, J.; Richardson, A.; Kiss, M.; Depiesse, F.; Murray, A. (British Journal of Sports Medicine, 2021)
Background Injuries and illnesses represent a health problem affecting athletics athletes` training and performance. Recently, research on injury and illness epidemiology and risk factors have provided some insights to help implement prevention strategies. The next step is presenting the science, in an engaging form that can assist medical teams, coaches and athletes understand and implement these strategies.